2019
DOI: 10.2298/tsci180512020p
|View full text |Cite
|
Sign up to set email alerts
|

A thermal model for open-rack mounted photovoltaic modules based on empirical correlations for natural and forced convection

Abstract: This paper proposes a thermal model for calculating the temperature of open-rack mounted photovoltaic (PV) modules taking into account the meteorological conditions, position (i. e. the inclination of one PV module and the angle between its surface and wind direction) and technical characteristics of the PV modules. The present model is valid for the steady-state operation and is based on the energy balance equation in which the forced convection is modelled by the new empirical correlations. The possibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The results showed that some of the models were more adapted to different weather. Alternatively, Perović et al 25 choose to develop a thermal model for open rack mounted PV module based on empirical correlation for natural and forced convection. The model included inclination of the PV module and wind direction, in addition to other meteorological conditions.…”
Section: Temperature Forecasting and Modelingmentioning
confidence: 99%
“…The results showed that some of the models were more adapted to different weather. Alternatively, Perović et al 25 choose to develop a thermal model for open rack mounted PV module based on empirical correlation for natural and forced convection. The model included inclination of the PV module and wind direction, in addition to other meteorological conditions.…”
Section: Temperature Forecasting and Modelingmentioning
confidence: 99%
“…In addition, two other models for determining the temperature distribution in the PV module and the output power are included. The temperature distribution in the PV module was calculated using the Ansys Transient Thermal software package, and the already confirmed empirical equation [10,[24][25][26][27][28][29] was used to calculate the output power of the PV module. In addition to validating the presented dynamic thermo-electric model, the importance of accuracy of measuring devices and optical losses is also included.…”
Section: Aims and Specifics Of The Current Researchmentioning
confidence: 99%
“…The CFD simulation study of the threedimensional flow fields around the photovoltaic cell is also suitable for studying the power generation efficiency of low solar radiation conditions and the influence of surface contamination on photovoltaic cells' power [10][11][12]. Perovic et al proposed a thermal model to model the temperature of photovoltaic cells according to the meteorological conditions, the locations of the photovoltaic cells, and their technical characteristics and determined their power and efficiency with consideration of their predicted temperatures [13]. Zhiqiang and Dongyang proposed a neural networkbased photovoltaic power prediction model based on the Hilbert transform and frequency entropy to solve the problem that the power fluctuations from photovoltaic power stations affect the dispatch operations and stability of the power grid incorporating substantial percentages of photovoltaic power [14].…”
Section: Introductionmentioning
confidence: 99%